PENGARUH KOMITMEN PROFESI, SOSIALISASI ANTISIPATIF MAHASISWA AKUNTANSI DAN ETHICAL CLIMATE PRINCIPLE TERHADAP NIAT WHISTLEBLOWING - hadi mahmudah (Universitas Lancang Kuning, 2018)
Whistleblowing is one of the company's internal control mechanisms. In practice many employees do not want to report fraud that occurred in the company. This study examines the influence of professional commitment, anticipatory socialization of accounting students and ethical climate principle towards whistleblowing intentions. The sample of this research is 6th semester accounting student in Jabodetabek which amounts to 125. Data is processed using multiple regressions. The results showed that professional commitment, anticipatory socialization of accounting students and ethical climate principle influenced the intention of whistleblowing. Keywords: whistleblowing, professional commitment, anticipatory socialization, and ethical climate principle.